High VLA-4 expression is associated with adverse outcome and distinct gene expression changes in childhood B-cell precursor acute lymphoblastic leukemia at first relapse - Shalapour, S.; Hof, J.; Kirschner-Schwabe, R.; Bastian, L.; Eckert, C.; Prada, J.; Henze, G.; von Stackelberg, A.; Seeger, K. (Haematologica (Roma), 2011)
Resistance to therapy and subsequent relapse remain major challenges in the clinical management of relapsed childhood acute lymphoblastic leukemia. As the bone marrow environment plays an important role in survival and chemotherapy resistance of leukemia cells by activating different signaling pathways, such as the VLA-4 and PI3K/Akt pathways, we studied the prognostic and biological impact of VLA-4 expression in leukemia cells from children with relapsed B-cell precursor acute lymphoblastic leukemia and its influence on the sensitivity of the leukemia cells to drugs. VLA-4 expression was quantified by real-time polymerase chain reaction in leukemia cells from 56 patients with relapsed acute lymphoblastic leukemia enrolled in the ALL-REZ BFM 2002 trial of the Berlin-Frankfurt-Münster study group. Gene expression changes related to VLA-4 expression were investigated by microarray-based mRNA profiling. The effect of VLA-4 signaling on proliferation and drug resistance was studied in co-cultures of leukemia and stromal cells. High expression of VLA-4 at first relapse was associated with adverse prognostic factors, poor molecular response to therapy and significantly worse probabilities of event-free and overall survival. VLA-4 expression was an independent prognostic parameter. Comparing gene expression profiles of leukemia cells with high versus low VLA-4 expression, we identified 27 differentially expressed genes primarily involved in the PI3K/Akt, ephrin and Rho GTPase pathways. Blocking of VLA-4 signaling in combination with cytarabine treatment abolished the growth supportive effect of stromal cells. Our results show that high VLA-4 expression is a marker of poor prognosis and a potential therapeutic target in children with relapsed acute lymphoblastic leukemia and confirm that cellular interactions and biological effects related to VLA-4 play a decisive role in the survival of leukemia cells and response to therapy. (ClinicalTrials.gov identifier: NCT00114348).